Design of Pure Sine Wave Inverter with Automatic Transfer Switch for Hybrid Solar Power Plant - ningrum, hanifah nur kumala (Universitas Trunojoyo Madura, 2024)
An inverter is an electronic device that converts direct current (DC) into alternating current (AC). The output of an inverter is an AC voltage in the form of a square wave, modified sine wave, and pure sine wave. In this research, an inverter with pure sine waveform with 220 VAC rms and 50 Hz frequency. An Automatic Transfer Switch (ATS) is needed to automatically divert electrical power from the Solar Inverter into the AC main source and vice versa. This ATS works when the battery capacity from a solar battery is decreased, the power source is switched to the AC main source , and diverted to a solar inverter when the battery capacity is under 50%. In this research, 184 watts of load is tested on performing the pure sine wave inverter. The ATS works properly to divert the source and needs a 5-second time delay when diverting the AC main source to a solar inverter, and a 1-second time delay when diverting from a solar inverter to an AC main source.